Highlights from the 9th Cachexia Conference. Issue 3 (June 2017) - Ebner, Nicole; von Haehling, Stephan
Abstract: This article highlights updates of pathways as well as pre‐clinical and clinical studies into the field of wasting disorders that were presented at the 9th Cachexia Conference held in Berlin, Germany, December 2016. This year, some interesting results from clinical trials and different new therapeutic targets were shown. This article presents the biological and clinical significance of different markers and new diagnostic tools and cut‐offs of detecting skeletal muscle wasting. Effective treatments of cachexia and wasting disorders are urgently needed in order to improve the patients' quality of life and their survival.